Service Quality in Public Transport Services of the Provicial Intercity Transportation (AKDP) in East Java Indonesia - Sukesi Sukesi; Eddy Yunus (Budapest International Research and Critics University, 2018)
Evaluating and increasing the quality of public transport services, especially in the transport of AKDP in East Java is necessary. This study tries to (1) identify and analyze the quality of services; (2) to see the result of community satisfaction survey index (SKM); (3) The highest and lowest effects of the variables on the result of SKM index. The elements of assessment and qualitative descriptive analysis tools refer to KEP / 25 / M.PAN / 2/2004 on guidelines for the preparation of the Community Satisfaction Index and the Ministry decree No. 16 Year 2014, with nine (9) elements of the SKM assessment. This study determines the accidental sample by a random sampling technique that was done proportionally on 221 respondents.